Case report: Minimally invasive primary debulking surgery for advanced stage epithelial ovarian cancer - Wolf, Jennifer; Goncalves, Nicole; Alagkiozidis, Ioannis (Frontiers in Oncology, 2024)
The surgical management of advanced ovarian cancer has historically emphasized an open technique, but advances in minimally invasive surgery (MIS) have led to its increasing use in ovarian cancer. Most research has focused on the utility of MIS in the interval debulking setting. Here, we present a case of a 38-year-old patient with incidentally diagnosed advanced stage ovarian cancer. We describe the robotic surgery techniques used to achieve complete primary cytoreduction, including resection of disease on the diaphragm. The patient has completed standard adjuvant chemotherapy and maintenance treatment and remains without evidence of disease for more than 2 years. This case details the techniques utilized to achieve complete cytoreduction including trocar placement, robotic instrument preference, and rotation of the robotic boom. This patient has had successful perioperative and oncologic outcomes, and her case highlights the role for minimally invasive primary debulking surgery for select patients with advanced ovarian cancer.